Avocado (Persea americana Mill.) seeds compounds affect Helicobacter pylori infection and gastric adenocarcinoma cells growth. (December 2022) - Athaydes, Brena Ramos; Tosta, Cristina; Carminati, Raffaela Zunti; Kuster, Ricardo Machado; Kitagawa, Rodrigo Rezende; Gonçalves, Rita de Cássia Ribeiro
Graphical abstract: Highlights: Avocado seeds have high antioxidant activity due to its phenolic compounds. Samples presented immunomodulatory activity, mainly by inhibiting IL-6 cytokine. SEAP showed better results and has gastric antitumor activity with low toxicity. Abstract: This study evaluated the effect of hydroalcoholic extract from avocado ( Persea americana Mill.) seeds (SCE), and its fractions, ethyl acetate (SEAP) and hexane (SHP), against Helicobacter pylori infection, its pathological process, and adenocarcinoma cells. Treatment with SEAP and SHP in H. pylori strains showed MIC and MBC ranging from 128 to 256 μg/mL and the presence of blebs and membrane deformations in scanning electron microscopy. SEAP presented IC50 of 55.43 ± 6.20 µg/mL and SHP of 11.80 ± 1.75 µg/mL against adenocarcinoma cells. SEAP presented higher antioxidant and immunomodulatory activity in the superoxide anion, hydrogen peroxide, hypochlorous acid inhibition, and Interleukin-6 assays. Chemical analysis using (-)-ESI-FTICR-MS of SEAP revealed the presence of catechin/epicatechin and polyhydroxylated fatty alcohols such as avocadene and avocadyne and, their acetates. Thus, the seeds of P. americana Mill. can become a natural alternative as an adjuvant in the treatment of gastric diseases, modulating different pathways involved in this process.